Integration of Digital Technologies and Investments in the Modernization of Industrial Sectors - Abdumajidova , Nozima (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This thesis analyzes the impact of the integration of investment resources and digital technologies on economic efficiency in the process of industrial modernization. Based on the dynamics of investments in fixed capital in Uzbekistan, the structural directions of investments are assessed and the insufficient level of digitalization is identified. The study develops scientific and practical recommendations to enhance the integration of investments and digital technologies.